Social media for public participation in urban planning in China based on place attachment-- a case of the Guangzhou banyan tree incident - Ouyang, Yifei; Bai, Xiaohe (Frontiers in Built Environment, 2025)
Given the current low level of public participation and limited channels of participation in Chinese urban planning. Social media has become an important platform for public participation in China. Taking the banyan tree relocation and felling incident in Guangzhou City as an example. This paper explores how social media-facilitated public participation can effectively influence urban planning decisions through case study and discourse power analysis. It is found that place attachment may serve as a significant motivator for public participation in urban planning. Social media plays a dual role in this process. On one hand, it can improve the effectiveness of public participation in urban planning and ultimately fulfil the role of advancing democratic government decision-making. On the other hand, the paper reveals challenges such as information homogenization, emotionalized communication, and elite dominance. These issues underscore the need for further improvements in regulatory mechanisms and technical support. Therefore, future urban planning policies should take people's emotions into account, and also need to accelerate the construction of improved systems, mechanisms and technologies for social media public participation to achieve high-level public participation goals.